Linguistic competence and cross-cultural negotiations: A Mexican-Norwegian example - Bjørge, Anne Kari; Natlandsmyr, Jan Halvor (HERMES - Journal of Language and Communication in Business, 2017)
In the present paper we look at the connection between level of linguistic competence and negotiation outcome in cross-cultural negotiations. The corpus consists of six Mexican-Norwegian dyads participating in a negotiation simulation. The language of communication was English, which means that none of the participants negotiated in their native language. The negotiation transcripts were submitted to a qualitative linguistic analysis and graded according to level of competence. These results were coupled to negotiation outcome, which was calculated according to a cost matrix. The findings showed no statistically significant connection between language competence and outcome.